IMPLEMENTATION OF MARKET DAY ACTIVITIES IN GROWING ENTREPRENEURIAL CHARACTER FOR MIN 3 GUNUNGKIDUL STUDENTS - Hartati, Sri; Anwar, Khoirul; Musidah, Siti; Nurhuda, Abid (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Entrepreneurial character building can be developed in children from elementary school. This study intends to describe how to implement market activities at MIN 3 Gunungkidul and how to grow entrepreneurial character values for students. The growth of this entrepreneurial character is carried out to realize the vision of MIN 3 Gunungkidul, in creating skilled students, and realizing the mission of